Концепція естетики в архітектурі. “традиційна” і “академічна” архітектура - Марковський, А. І.; Markovskyi, A. (Видавництво Львівської політехніки, 2018)
Подано передумови виникнення сучасних критеріїв у естетиці щодо архітектури на тлі кризи у мистецтві в першій половині ХХ століття. Розглянуто категорії “краси” та “корисності” в архітектурі, як місці синтезу мистецтва та інженерних наук. Наведено дефініцію “традиційної”, “академічної” та “сучасної” архітектури

Architecture from the aesthetics criteria point of view is in unique position, is being the high art and utilitarian, material thing at the same time. The famous formula of Vitruvius, “utilitas, firmitas, venustas” [utility, strength, beauty] reveals synthesis of spirit and matter. Architecture, that have been a monumental art, at the same time is very visual: it is constantly around us, has created habitat and acquiring in this way has the obvious superiority in case of influence on people. Monuments, that have extant, first was proclaimed as a landmarks of the epoch: their creating requires considerable investments and global efforts of cohesive society, sublimates a whole baggage of advanced scientific and aesthetic searches, that was available at the moment. Architect, with few exceptions, can not exist as an active agent of the field without proper recognition, acceptance of his work by the public. So architecture that is realized automatically becomes a reflection of aesthetic preferences that prevail in one or another society at a certain time. Crystallization of the concept of “traditional” and “academic” art began to form at the border of nineteenth and twentieth centuries. This was due, on the one hand, by national liberation tendencies in Central and Eastern Europe, where, in line of the recovery of self-definition and national identity searches, the explorers began to carefully research and collect samples of traditional folk art. On the other hand - a rapid colonial and research expansion of Western European countries, which opened to European artists a rich layer of art of the East, the tribes of Africa, Oceania and America (at that time classification: “primary” or “primitive” art). “For early twentieth century art an opening of primitive society cultures, the revaluation of heritage of the medieval Europe and the East, archaeological findings in Egypt, Mesopotamia, India, have provided powerful impulses in the search for a new artistic language, which have significantly differed from the usual system of European classical fine art” [4, p. 139-140]. At the same time with the opening of the other cultures traditions and research of its own historical heritage, had raises the question of self-definitions of the concepts of “traditional” and “nontraditional” (“academic”) art. Still there is no exact definitions and clear limits for these concepts and they can considerably differ for variety kinds of art at different countries and regions. If we are talking about the architecture of Europe, in a broad sense, traditional architecture is the architecture that was built by folk masters from traditional materials, according to the traditions of a cultural area. The twofold nature of architecture, that associated with arts and practical engineering aspects simultaneously, have complicated the issue. This leads to the aftereffect that architects are often divided into two conditional subgroups: “theoreticians” and “practitioners”. The first are accused of lack of practice, which from the standpoint of their opponent eventually undermine their role in the development of architecture as a phenomenon. Practitioners in contrast, often venturing into application activity, leave society very few information about stimulus and motives of their own creative method. In this regard, the architecture is quite different from other plastic arts, because require from the viewer a relevant knowledge not only in theoretical aesthetics, but also in the engineering sector, which significantly reduces the number of qualified critics. This means in our opinion that the question of “aesthetics” in architecture is quite different from the others arts and beyond the scope of the philosophical categories of “beauty”, “taste” and “culture”. According to Vitruvius, as has been said before, “beauty” in architecture is defined through its “utility” and “strength”. This concept now dominates in academic criteria of architecture that paradoxically is in common criteria between “academic” and “applied” art. The obligatory functionality and practicality of “high” “academic” architecture (even the most radical architectural concept should take into account gravity, carrying capacity of material and other physical components) by a straight line connect it with the “traditional” and “applied” architecture. Accordingly, the definition of aesthetics in contemporary architecture can not be defined only as a theoretical category and should obligatorily take into account a practical experience
The concept of aesthetics in architecture. “traditional” and “academic” architecture
Keywords: естетика; мистецтво; культура; краса; традиційна архітектура; архітектура сучасна; aesthetics; art; culture; beauty; traditional architecture; modern architecture; 72.01. (477)